Proposal for reaching out students in distance learning: A new universities subject at the Universidad Estatal a Distancia in Costa Rica (Ágora de Heterodoxias, 2016)
The State University of Distance Education of Costa Rica (hereinafter UNED-C.R.) has been outlining its students population from traditional characteristics, as if they were part of a traditional face-to-face classroom university system, favoring in the student a way of thinking and a way by which he perceives himself.. From the creation of the Research System at UNED perspectives change. This paper aims to propose a new way of looking at students beyond the traditional characteristics in which the university has enclosed them, and value to all the baggage of knowledge and experiences throughout their lives.  Below, it is presented a preview of the results achieved with a population of 46 students   in a distance education model. They participated in different face-to-face and virtual activities where they developed their broad profile and represented –with the help of technological tools- the networks of their living environment.  At the end of the experience, a total of 9 individuals achieved self-reflection processes and shared with peers their resignified profiles as multiple connections university subjects.  All the above was possible with the help of three tools:  the concept of metanoia, broad profiles and student networks. Although the results are inconclusive, it is proven that it is possible and necessary to consider alternative models that lead to look at the student in a different way, more strengthened, and to think about him beyond the traditional characterizations that place him as one more indicator.
Keywords: metanoia; broad profiles; student networks; UNED; distance education